Hadis Iftirāq dalam Literatur Otoritatif: Potret Jaringan dan Kepentingan - Miski, Miski (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2022)
Iftirāq hadith creates its own problems. The hadith is used as a tool that triggers internal religious conflicts, truth claims, and stereotypes, and so on. Moreover, the hadith is also found in Sunan Abū Dāwūd, Sunan al-Tirmiżī, and Sunan Ibn Mājah; three authoritative sunan in hadith scholarship. It is important to look at this from the most basic aspect, namely how sources of transmission, networks, and socio-political-cultural contexts surround the existence of the iftirāq hadith. This study uses the three Sunan as primary data; in tracing the related hadiths, this study uses the takhrīj method; supported by other relevant data; all of these data were analyzed by descriptive and socio-historical methods. This study also has three main findings. First, the iftirāq hadith networks in the three Sunans tend to be diverse, although one of the three networks is correlated with the same narrator, namely, Abū Hurairah. Second, the source of iftirāq hadith transmission cannot be separated from the riḥlah tradition that existed at that time; this allowed all three to meet the narrators of the hadith. Third, the existence of the iftirāq hadith cannot be separated from the context at that time which tended to be conflicted; from the interests of confirming identity to the struggle for authority between religious groups.